Optimizing the Anticipation of Problematic Gadget Use in Children by Utilizing Artificial Intelligence Technology at SMPN 23 Bekasi City (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The objective of this community service (Pengabdian kepada Masyarakat - PKM) program was to increase awareness of problematic gadget use and optimize the role of teachers in educating students to use gadgets productively. The program was implemented from July to September 2025, targeting 20 students, 10 teachers, and 20 students' parents. To achieve its goals, the PKM team employed several strategies, including engaging 20 students' parents in prevention and management efforts, providing counseling services for students exhibiting problematic gadget use, enhancing the IT skills of teachers and students, and establishing a healthy digital community within the school environment. Healthy gadget use in this context is defined as limited screen time, adherence to rules such as the 20-20-20 rule, and balancing usage with physical activities and direct social interaction. Conversely, negative gadget use refers to excessive usage that causes various problems, whether mental, physical, or academic. Based on an evaluation conducted through pre-test and post-test questionnaires administered before and after the program, the students' level of Problematic Gadget Use (PGU) was significantly reduced. The measurement tool used was a standardized questionnaire previously validated and found reliable (with a Cronbach's Alpha of 0.886) in a similar population, ensuring data accuracy. Before the PKM, the average PGU score for SMP Negeri 23 students was at a moderate level. Before the training, the students' negative gadget use level was 53.86%, and afterward, it dropped to 29.67%, placing it in the low category. Regarding the level of understanding among teachers and students concerning Artificial Intelligence (AI) technology, the average pre-test score was 56.80%, categorized as moderate. This score increased to 86.36% post-PKM, reaching the high category. For the aspect of teachers' understanding regarding the anticipation of problematic gadget use, the average pre-test score was 44.53% (moderate category), which increased significantly to 82.80% (high category) after the program implementation.